SEMINAR PARENTING “MEMPERSIAPKAN ANAK MASUK SEKOLAH DASAR” - Ika Apriati Widya Puteri (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
At the age of 4-6 years many parents choose to send their children to school. Some parents do that because awareness of the importance of preschool education, some are because both parents work. Another reason is to prepare children to enter the elementary school. School readiness is defined as a child's ability to achieve an adequate level of emotional, physical and cognitive development so that the child is able to do well in school. Factors that influence children's school readiness are family environmetl, parental roles, and maturity. However, many parents are more focused on academic skills such as reading, writing, and arithmetic on preparing for school readiness. This results in many children lack of readiness like emotionally immature when they enter elementary school, and show behaviors such as unable to cooperate with friends and teachers, having difficulty communicating with others, and having behavioral problems at school. To help parents understand how to prepare children to enter elementary school, the authors view seminars as a method that can be used to provide knowledge and psychoeducation for parents. Participants were 20 parents of students at Al Azhar 5 Samarinda Islamic Kindergarten. The conclusions are many parents still do not understand that the readiness of their children to enter elementary school is not just an academic matter. Maturity is one factor that is quite important so that children are ready to undergo education in elementary school and are able to successfully carry out this level of education.